Infliximab biosimilar CT-P13 therapy is effective in maintaining endoscopic remission in ulcerative colitis – results from multicenter observational cohort. (2nd November 2018) - Bálint, Anita; Rutka, Mariann; Kolar, Martin; Bortlik, Martin; Duricova, Dana; Hruba, Veronika; Lukas, Martin; Mitrova, Katarina; Malickova, Karin; Lukas, Milan; Szepes, Zoltán; Nagy, Ferenc; et al.
ABSTRACT: Background : CT-P13, the first biosimilar monoclonal antibody to infliximab (IFX), has previously been confirmed to be efficacious in inducing mucosal healing in ulcerative colitis (UC) patients. The aim of this study was to evaluate the efficacy of CT-P13 therapy in maintaining mucosal healing in UC. Methods : CT-P13 trough levels, antibody positivity, serum inflammatory markers as CRP level, fecal calprotectin at weeks 14 and 54, concomitant steroid and azathioprine therapy at the time of induction therapy and at weeks 14 and 54, previous use of anti TNF drug and the need of dose intensification as possible predictive factors for mucosal healing at week 54 were evaluated in this prospective study. Results : 61 patients had already completed the 54-week treatment period. Mucosal healing was shown in 65.5 % and 62.1 %, complete mucosal healing was present in 31% and 38 % at week 14 and 54, respectively. The median values of CRP, leukocytes, thrombocytes, and albumin showed significant difference between baseline and week 54. Serum antibody positivity was proved in 6.5 % and 19.7 % of cases at week 14 and 54, respectively. Conclusion : Our study confirmed the long-term efficacy of CT-P13 therapy on mucosal healing in UC.